INSECTICIDAL ACTIVITY OF Cunila angustifolia ON Acanthoscelides obtectus - Savaris, Marcoandre (2012)
The use of extracts and essential oils of plants has been used as an important alternative to control insect pests of stored grains. The aim of this study was to evaluate the insecticide effect of extracts and the essential oil of C. angustifolia on adults of A. obtectus, under laboratory conditions. The experiment was conducted at random design with four replications, being tested crude and aqueous extracts, hexanic fraction and essential oil of C. angustifolia, at the doses of 0.001, 0.002, 0.004 and 0.008 mL cm-2. Each replicate received 10 adults of A. obtectus. Mortality of these insects was recorded the 24, 48, 72, 96 and 120 hours after application. All doses of the essential oil of C. angustifolia achieved 100% of efficiency in the mortality of A. obtectus after 24 hours. The other treatments showed low control efficiency when they were compared to the effect of essential oil. This research demonstrates the insecticide activity of the essential oil of C. angustifolia proving to be promising in the control of this primary pest.